2014
DOI: 10.1128/aem.01282-14
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oxidative Stress in Sclerotial Differentiation and Aflatoxin B1 Biosynthesis in Aspergillus flavus

Abstract: cWe show here that oxidative stress is involved in both sclerotial differentiation (SD) and aflatoxin B1 biosynthesis in Aspergillus flavus. Specifically, we observed that (i) oxidative stress regulates SD, as implied by its inhibition by antioxidant modulators of reactive oxygen species and thiol redox state, and that (ii) aflatoxin B1 biosynthesis and SD are comodulated by oxidative stress. However, aflatoxin B1 biosynthesis is inhibited by lower stress levels compared to SD, as shown by comparison to undiff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 57 publications
1
75
1
5
Order By: Relevance
“…Relative humidity, temperature, substrate (growth medium), number of fungal spores inoculated and oxidation stress are the main factors influencing fungal growth, metabolism and MVOCs' production in a laboratory setting [20][21][22]. For example, López-Malo et al [23] studied the effect of incubation temperature (10-30˝C), pH (3.0-4.0) and vanillin concentration (350-1200 ppm) on the growth of A. flavus.…”
Section: Introductionmentioning
confidence: 99%
“…Relative humidity, temperature, substrate (growth medium), number of fungal spores inoculated and oxidation stress are the main factors influencing fungal growth, metabolism and MVOCs' production in a laboratory setting [20][21][22]. For example, López-Malo et al [23] studied the effect of incubation temperature (10-30˝C), pH (3.0-4.0) and vanillin concentration (350-1200 ppm) on the growth of A. flavus.…”
Section: Introductionmentioning
confidence: 99%
“…An intriguing relation between oxidative stress, secondary metabolite production and sexual development has been unfolding during the last few years in Aspergillus, which was initiated by the work of Reverberi et al (2007) on Aspergillus parasiticus and Aspergillus ochraceus, and further studied by many others (Baidya et al, 2014;Grintzalis et al, 2014;Reverberi et al, 2012;Wartenberg et al, 2012;Yin et al, 2013). In A. nidulans, the stress response proteins NapA and DlpA have been shown to play a role in developmental processes and sterigmatocystin production (Wartenberg et al, 2012;Yin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…AFB 1 biosynthesis is controlled by a wider array of oxidative stress factors, such as lipid hydroperoxide, superoxide, and hydroxyl and thiol radicals (Grintzalis et al, 2014). Grintzalis et al 2014 observed that (i) oxidative stress regulates fungal sexual development, as implied by its inhibition by ROS and thiol redox state, and that (ii) the AFB 1 biosynthesis and sexual development are coregulated by the oxidative stress. Numerous studies have shown that the AF production can be exacerbated by ROS and their reactive products including oxylipins and peroxidized lipids (Fabbri et al, 1983;Gao and Kolomiets, 2009).…”
Section: Environmental Factors Affecting Aflatoxin Biosynthesismentioning
confidence: 99%
“…AF production apparently could direct the ROS excess accumulated during cell ageing, or as a response to external insults, into extending the fungal lifespan (Hong et al, 2013). AFB 1 biosynthesis is controlled by a wider array of oxidative stress factors, such as lipid hydroperoxide, superoxide, and hydroxyl and thiol radicals (Grintzalis et al, 2014). Grintzalis et al 2014 observed that (i) oxidative stress regulates fungal sexual development, as implied by its inhibition by ROS and thiol redox state, and that (ii) the AFB 1 biosynthesis and sexual development are coregulated by the oxidative stress.…”
Section: Environmental Factors Affecting Aflatoxin Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation